Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1365-2796.2011.02472.x
|View full text |Cite
|
Sign up to set email alerts
|

A myocardial infarction genetic risk score is associated with markers of carotid atherosclerosis

Abstract: Abstract. Hamrefors V, Hedblad B, Engström G, Almgren P, Sjögren M, Melander O (Lund University, Malmö, Sweden). A myocardial infarction genetic risk score is associated with markers of carotid atherosclerosis. J Intern Med 2012;271: 271-281.Objective. To assess whether or not a genetic risk score that was previously shown to be associated with myocardial infarction (MI) and coronary artery disease (CAD) is also associated with markers of carotid atherosclerosis.Design. A total of 4022 middle-aged subjects fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…These findings are in accordance with those of our study, indicating the promising role in CI of both loci. Furthermore, rs4977574 and rs2383206 polymorphisms were associated with a thicker IMT or carotid atherogenesis among the middle-aged Caucasians 36,37) . Because asymptomatic or subclinical plaque development is becoming a more accurate predictor of AS than IMT 38) , variants on chromosome 9p21 probably confer risks of acute CI in the Chinese Han population.…”
Section: Genotype Frequencies In Patients With CI With or Without Carmentioning
confidence: 99%
“…These findings are in accordance with those of our study, indicating the promising role in CI of both loci. Furthermore, rs4977574 and rs2383206 polymorphisms were associated with a thicker IMT or carotid atherogenesis among the middle-aged Caucasians 36,37) . Because asymptomatic or subclinical plaque development is becoming a more accurate predictor of AS than IMT 38) , variants on chromosome 9p21 probably confer risks of acute CI in the Chinese Han population.…”
Section: Genotype Frequencies In Patients With CI With or Without Carmentioning
confidence: 99%
“…Of the two community‐based genetic score studies referred in the previous section, the subjects in the second (Finnish) study were younger on average and this study also showed the strongest predictive utility of the GRS (Tikkanen et al ., ). Moreover, in a population‐based study of 4000 middle aged subjects, 97·5% of whom were free of overt CVD, we found that a CAD GRS was strongly associated with occurrence of small carotid plaques (Hamrefors et al ., ), further supporting the hypothesis that genetic variants affect the atherosclerotic process in an early stage. Thus, common genetics may be a potential tool for identifying subjects at future high risk of CAD and atherosclerosis already before atherosclerotic markers could be detected by imaging.…”
Section: The Clinical Value Of Cad Geneticsmentioning
confidence: 97%
“…As an example of implementation, a nine loci lipid GRS was shown to strongly predict incident CVD also after adjusting for baseline lipid levels (Kathiresan et al, 2008). The same concept has been imple-mented also in studies of blood pressure and CAD (Ripatti et al, 2010;Hamrefors et al, 2012;Hughes et al, 2012;Ganna et al, 2013;Tikkanen et al, 2013;Mega et al, 2015a) with various results. It should be clarified that the concept of GRS, simple as it may seem, has a number of limitations.…”
Section: Genetetic Findings In Cadmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Multilocus genetic risk scores (GRS) combining multiple SNPs with modest effects on cardiovascular risk have been shown to predict incident cardiovascular events in several prospective cohorts of European ancestry. 310 GRSs based on common CAD risk variants have been associated with atherosclerotic phenotypes such as peripheral artery disease 11 and carotid intima-media thickness 12 , and coronary artery calcium 5 , an indirect measure of atherosclerotic burden.…”
mentioning
confidence: 99%